2005
DOI: 10.1016/j.stam.2004.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Surface hydration states of commercial high purity α-Al2O3powders evaluated by temperature programmed desorption mass spectrometry and diffuse reflectance infrared Fourier transform spectroscopy

Abstract: The surface of three different grades of commercial high-purity a-Al 2 O 3 powders produced by hydrolysis of aluminum alkoxide, which differ each other in SSA are evaluated by temperature programmed desorption mass spectrometry (TPDMS) and diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. For the DRIFT evaluation the powders were heated in situ under vacuum from 25 to 700 8C. The TPDMS spectra of desorbed H 2 O were obtained by heating the samples under ultra high vacuum at a rate of 20 K mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…One can see that there are likely to be many singly coordinated surface hydroxyl groups. Investigators have identified the surface hydroxyl groups found on several types of submicron α‐alumina powders to be similar to those found on gibbsite and/or other aluminum hydroxides 51,52 …”
Section: Single Crystal Alumina Surfaces Versus Powdermentioning
confidence: 97%
See 4 more Smart Citations
“…One can see that there are likely to be many singly coordinated surface hydroxyl groups. Investigators have identified the surface hydroxyl groups found on several types of submicron α‐alumina powders to be similar to those found on gibbsite and/or other aluminum hydroxides 51,52 …”
Section: Single Crystal Alumina Surfaces Versus Powdermentioning
confidence: 97%
“…The surface of submicron powder is somewhat different than single crystal samples because the majority of the surface sites on the powders are defect sites 49,50 . Also, the surface of alumina powders prepared by grinding or milling (the majority of alumina is used after some milling) can have surface hydroxyl groups that are the same as those on gibbsite 51,52 …”
Section: Surface Hydration Charging and Surface Ionization Reacmentioning
confidence: 99%
See 3 more Smart Citations